An industrial case study on discrete event modelling of value stream mapping for Industry 4.0. (4th July 2020) - Lim, Theodore; Linnenbrink, Mathis; Ritchie, James; Sivanathan, Aparajithan; Harper, Sam; Teichert, Carsten; Waller, Anthony
Discrete event modelling (DEM) can describe the behaviour and performance of a real-life activity or process within a facility or system that occurs over time. This work reports on applying DEM as a tool to provide fundamental insights on how small and medium-sized enterprises (SME's) can incrementally improve their capability regarding the implementation of an Industry 4.0 strategy. The case study discussed analyses the potential changes to the project life cycle of an SME as it undertakes a journey towards implementing Industry 4.0 for its operations. A combination of value stream mapping (VSM) and data stream mapping (DSM) enabled holistic mapping of the SME's project's life cycle into discrete event stages, which were integrated on the WITNESS DEM system to enable the company to stress test and plan their Industry 4.0 implementation strategy over time. The findings reveal the interdependent nature of workforce and technology necessitates simultaneous development to achieve optimal functionality.